Outer Hair Cell and Auditory Nerve Function in Speech Recognition in Quiet and in Background Noise - Hoben, Richard; Easow, Gifty; Pevzner, Sofia; Parker, Mark A. (Frontiers in Neuroscience, 2017)
The goal of this study was to describe the contribution of outer hair cells (OHCs) and the auditory nerve (AN) to speech understanding in quiet and in the presence of background noise. Fifty-three human subjects with hearing ranging from normal to moderate sensorineural hearing loss were assayed for both speech in quiet (Word Recognition) and speech in noise (QuickSIN test) performance. Their scores were correlated with OHC function as assessed via distortion product otoacoustic emissions, and AN function as measured by amplitude, latency, and threshold of the VIIIth cranial nerve Compound Action Potential (CAP) recorded during electrocochleography (ECochG). Speech and ECochG stimuli were presented at equivalent sensation levels in order to control for the degree of hearing sensitivity across patients. The results indicated that (1) OHC dysfunction was evident in the lower range of normal audiometric thresholds, which demonstrates that OHC damage can produce “Hidden Hearing Loss,” (2) AN dysfunction was evident beginning at mild levels of hearing loss, (3) when controlled for normal OHC function, persons exhibiting either high or low ECochG amplitudes exhibited no statistically significant differences in neither speech in quiet nor speech in noise performance, (4) speech in noise performance was correlated with OHC function, (5) hearing impaired subjects with OHC dysfunction exhibited better speech in quiet performance at or near threshold when stimuli were presented at equivalent sensation levels. These results show that OHC dysfunction contributes to hidden hearing loss, OHC function is required for optimum speech in noise performance, and those persons with sensorineural hearing loss exhibit better word discrimination in quiet at or near their audiometric thresholds than normal listeners.